Serum Vitamin D and B12 Levels in Alcoholic Male Patients: A Cross-sectional Study - Jayan, Archana; Pokhrel, Buddhi Raj; Gautam, Narayan; Jha, Amit Chandra; Tamang, Binaya; Shrestha, Jharana; Ranjan, Sanjeev; Dubey, Raju Kumar (Journal of Universal College of Medical Sciences, 2021)
INTRODUCTION Alcohol dependence is a global problem and is rapidly increasing in developing countries. We aimed to analyze the serum levels of vitamin B12 and vitamin D in chronic alcoholic patients and their association with parameters of liver function. MATERIAL AND METHODS A cross-sectional study was carried out in Universal College of Medical Sciences, Bhairahawa, Nepal from March 2020 to September 2020 on patients visiting the Psychiatric Out Patient Department (OPD) for the treatment of alcohol dependence. The patients were categorized as excessive and moderate drinkers. Serum vitamin B12, vitamin D, and hepatic function parameters were measured. RESULTS The median serum vitamin B12 and vitamin D levels were 467.8 pg/ml and 24.9 ng/ml respectively. Excessive drinkers had significantly higher B12 levels than moderate drinkers. Vitamin B12 levels correlated positively with liver function parameters, as well as alcohol amount and duration of consumption. Vitamin D levels were insufficient in 57 (71.25%) of the overall participants. CONCLUSION Serum levels of vitamin B12 are not affected in patients with alcohol dependence. Alcohol consumption, however, reduces serum concentrations of vitamin D. Vitamin B12 concentration is positively associated with liver enzymes and other parameters of liver function.